2022
DOI: 10.3389/fimmu.2022.866035
|View full text |Cite
|
Sign up to set email alerts
|

Serum Proteomic Analysis Identifies SAA1, FGA, SAP, and CETP as New Biomarkers for Eosinophilic Granulomatosis With Polyangiitis

Abstract: BackgroundEosinophilic granulomatosis with polyangiitis (EGPA) is characterized by asthma-like attacks in its early stage, which is easily misdiagnosed as severe asthma. Therefore, new biomarkers for the early diagnosis of EGPA are needed, especially for differentiating the diagnosis of asthma.ObjectivesTo identify serum biomarkers that can be used for early diagnosis of EGPA and to distinguish EGPA from severe asthma.MethodData-independent acquisition (DIA) analysis was performed to identify 45 healthy contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…For the PRM data, the intensity of each peptide was quantified by averaging the peak AUC of the top three fragment ions (b and y), and the average intensity of all the confidently identified peptides was used to calculate the protein intensity ( 35 ). For each sample, the protein with maximum intensity was used for normalization ( 36 ).…”
Section: Methodsmentioning
confidence: 99%
“…For the PRM data, the intensity of each peptide was quantified by averaging the peak AUC of the top three fragment ions (b and y), and the average intensity of all the confidently identified peptides was used to calculate the protein intensity ( 35 ). For each sample, the protein with maximum intensity was used for normalization ( 36 ).…”
Section: Methodsmentioning
confidence: 99%
“…We observed similar risk decreasing effects on asthma and CKD in European centric MR analysis of lower CETP protein concentration 5 . Lower plasma concentrations of CETP have been previously linked to asthma in non-randomized observational studies 40 . A clear biological rationale for CETP involvement in asthma or CKD is however currently absent, prohibiting a straightforward evaluation of the validity of the observed risk increasing effects in individuals of East Asian ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…Among the eight key genes identified for AAV kidney injury, CSF2 is involved in the pathogenesis of several inflammatory and autoimmune diseases, and play an essential role in regulating the pro-inflammatory function of monocytes in the pathogenesis of AAV-related renal injury ( Krebs et al, 2017 ; VVilar et al, 2020 ; Rousselle et al, 2022 ). Rousselle ( Jing et al, 2022 ) found that CSF2 increased the ability of ANCA-stimulated monocytes to produce interleukin (IL)-1β and promote Th17 effector cell polarization. FGA is a major plasma protein coagulation factor in the regulation of wound healing, tissue regeneration, and the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%